Polyethylene damage and deformation on fixed-bearing, non-conforming unicondylar knee replacements corresponding to progressive changes in alignment and fixation - Harman, Melinda K.; Schmitt, Sabine; Rössing, Sven; Banks, Scott A.; Scharf, Hanns-Peter; Viceconti, Marco; Hodge, W. Andrew (Clinical biomechanics, 2010)
Background - Deviations from nominal alignment of unicondylar knee replacements impact knee biomechanics, including the load and stress distribution at the articular contact surfaces. This study characterizes relationships between the biomechanical environment, distinguished by progressive changes in alignment and fixation, and articular damage and deformation in a consecutive series of retrieved unicondylar knee replacements. - Methods - Twenty seven fixed-bearing, non-conforming unicondylar knee replacements of one design were retrieved after 2 to 13years of in vivo function. The in vivo biomechanical environment was characterized by grading component migration measured from full-length radiographs and grading component fixation based on intraoperative manual palpation. Articular damage patterns and linear deformation on the polyethylene inserts were measured using optical photogrammetry and contact point digitization. - Findings - Articular damage patterns and surface deformation on the explanted polyethylene inserts corresponded to progressive changes in component alignment and fixation. Component migration produced higher deformation rates, whereas loosening contributed to larger damage areas but lower deformation rates. Migration and loosening of the femoral component, but not the tibial component, were factors contributing to large regions of abrasion concentrated on the articular periphery. - Interpretation - Classifying component migration and fixation at revision proved useful for distinguishing common biomechanical conditions associated with the varied polyethylene damage patterns and linear deformation for this fixed-bearing, non-conforming design. Pre-clinical evaluations of unicondylar knee replacements that are capable of reproducing variations in clinical alignment and predicting the observed wear mechanisms are necessary to better understand the impact of knee biomechanics and design on unicondylar knee replacement longevity.
Gesehen am 24.03.2023